2019
DOI: 10.1007/s42452-019-1500-6
|View full text |Cite
|
Sign up to set email alerts
|

A GIS–AHP-based approach in siting MSW landfills in Lokoja, Nigeria

Abstract: The acute shortage and scarcity of lands for suitable waste disposal is rapidly becoming a critical growing potential problem in most urban cities in developing countries of the world, and several fast-growing cities in Nigeria are not exempted from this menace. In this study, geographic information system (GIS) and analytic hierarchy process (AHP) are combined to select the most suitable landfill location in Lokoja, Nigeria. The landfill site selection criteria considered include proximity to major road, powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The presented approach assists decision-makers in selecting reliable locations for the safe disposal of MSW Santosh & Sivakumar Babu, 2018). In their study, Adewumi et al (2019) implemented the GIS and the analytic hierarchy process (AHP) to select the most suitable landfill location in Lokoja, Nigeria. The result will greatly serve as a guide in landfill site selection in major urban states of other developing countries (Adewumi et al, 2019).…”
Section: Public Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented approach assists decision-makers in selecting reliable locations for the safe disposal of MSW Santosh & Sivakumar Babu, 2018). In their study, Adewumi et al (2019) implemented the GIS and the analytic hierarchy process (AHP) to select the most suitable landfill location in Lokoja, Nigeria. The result will greatly serve as a guide in landfill site selection in major urban states of other developing countries (Adewumi et al, 2019).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…In their study, Adewumi et al (2019) implemented the GIS and the analytic hierarchy process (AHP) to select the most suitable landfill location in Lokoja, Nigeria. The result will greatly serve as a guide in landfill site selection in major urban states of other developing countries (Adewumi et al, 2019). Agrawal et al (2020) carried out a study to select a candidate landfill site for the city of Sultanpur using GIS and AHP.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Once the hierarchy has been established, a pair wise comparison matrix of each element within each level is constructed. This pair-wise comparison permits for an independent rating of each factor's contribution, which therefore simplify the decision-making process (Adewumi et al 2019). The eigenvalue of the comparison matrix gave the relative importance of the criteria being compared.…”
Section: Ahp Modelmentioning
confidence: 99%
“…RS plays a vital role in providing spatial thematic information including LULC, drainage, slopes, elevations, among others (Emun, 2010;Mussa & Suryabhagavan, 2019). Similarly, multi-criteria decision analysis (MCDA) based on Analytical Hierarchy Process (AHP) technique is extensively engaged to combine socio-economic, environmental, and technical aspects in analysing complex spatial related problems involving conflicting criteria (Adewumi et al, 2019;Ghanbarpour et al, 2013;Hwang & Lin, 2012) and is revealed as the most appropriate method for site selection (Coban et al, 2018;Ersoy & Bulut, 2009;Mutluturk & Karaguzel, 2007;Ş ener et al, 2010;Simsek et al, 2006;Yesilnacar & Cetin, 2008). The integration of GIS and the AHP technique has been a more powerful instrument to solve landfill selection problems (Allen et al, 2003;Ş ener et al, 2006).…”
Section: Introductionmentioning
confidence: 99%